2014
DOI: 10.1021/ja510998s
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Probes for Tracking the Transfer of Iron–Sulfur Cluster and Other Metal Cofactors in Biosynthetic Reaction Pathways

Abstract: Iron–sulfur (Fe–S) clusters are protein cofactors that are constructed and delivered to target proteins by elaborate biosynthetic machinery. Mechanistic insights into these processes have been limited by the lack of sensitive probes for tracking Fe–S cluster synthesis and transfer reactions. Here we present fusion protein- and intein-based fluorescent labeling strategies that can probe Fe–S cluster binding. The fluorescence is sensitive to different cluster types ([2Fe–2S] and [4Fe–4S] clusters), ligand enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 57 publications
3
27
0
Order By: Relevance
“…4A), suggesting that Php4 does not bind the cluster or alter the Fe-S cluster coordination environment under these conditions. The addition of 5 mM DTT to this mixture, which has been shown to accelerate Fe-S cluster transfer reactions, 31 also did not facilitate formation of the [2Fe-2S] Php4-Grx4 heterocomplex (data not shown). These results demonstrate that [2Fe-2S] Grx4 cannot be converted to the [2Fe-2S] Php4-Grx4 complex by simple titration with Php4.…”
Section: Resultsmentioning
confidence: 95%
“…4A), suggesting that Php4 does not bind the cluster or alter the Fe-S cluster coordination environment under these conditions. The addition of 5 mM DTT to this mixture, which has been shown to accelerate Fe-S cluster transfer reactions, 31 also did not facilitate formation of the [2Fe-2S] Php4-Grx4 heterocomplex (data not shown). These results demonstrate that [2Fe-2S] Grx4 cannot be converted to the [2Fe-2S] Php4-Grx4 complex by simple titration with Php4.…”
Section: Resultsmentioning
confidence: 95%
“…Recent studies have suggested formation of Fe–S cluster-associated high molecular weight species (HMWS) when excess DTT is added to the reaction mixtures after the formation of [2Fe–2S] clusters, which can then either facilitate cluster transfer between putative protein partners or formation of [4Fe–4S] cluster on scaffold proteins [49, 50]. To investigate the role of DTT in our studies, several control reactions were performed by incubating [2Fe–2S](GS) 4 complex, holo Nfu and holo ferredoxins with excess DTT.…”
Section: Discussionmentioning
confidence: 99%
“…These can then facilitate cluster transfer between putative protein partners or formation of [4Fe-4S] cluster on scaffold proteins if excess DTT is added after the formation of [2Fe-2S] clusters. 75, 76 In our studies, we incubated holo proteins (holo IscU, holo Isa1, holo Grx2, holo Grx3, holo ferredoxins, and [2Fe-2S](GS 4 ) complex) with excess DTT. No significant change in the CD signal of the holo proteins was observed, clearly indicating that under our conditions, DTT is not forming any intermediate Fe-S species.…”
Section: Discussionmentioning
confidence: 99%